The Effect of the Sensory-Motor Programme on Some Perceptual Motor Abilities Capacities among the Children autism - شعلال, اسماعيل مصطفى; شنوف , خالد (Journal of Human Sciences, 2022)
This research aims to propose a Sensory-motor program which develops some perceptual capacities abilities (balance, size, body image and its distinction) among autistic children between 6 and 9 years old.Our hypothesis wants to verify whether such a program positively affects motor perceptual abilities in this audience. The experimental method is adopted in addition to an earlier and later research method on a sample of 10 autistic children between 6 and 9 years old divided into two groups. A test (bordou) is carried out for such an experiment.The most important conclusion we have come to is that: the proposed Sensorimotor program positively affects the development of perceptual-motor skills of children with Autism.We recommend the use of this program in the preparation of adapted psychomotricity programs in centers for children with Autism.